Effects of aluminium toxicity on some biochemical components of rice (Oryza sativa L.) (Dhaka University Journal of Biological Sciences, 2020)
An experiment was conducted to investigate the effect of aluminium (Al) toxicity on reducing and total sugar, proline, total amino acid and protein in rice seedlings grown in solution culture and phenolic compounds, chlorophyll and carotenoids in rice plants grown in sand culture. Exposure of rice seedlings to different concentrations of aluminium (10 - 150 μM) led to a stimulation of reducing and total sugar in the root and the shoot. Similarly, Al stress increased proline and total amino acid contents in different parts of rice seedlings. Aluminium toxicity caused a significant increase in phenolic compounds in rice plants. On the other hand, aluminium stress resulted in a reduction of chlorophyll-a, chlorophyll-b and carotenoid contents in the leaves of rice plants.Dhaka Univ. J. Biol. Sci. 29(1): 125-132, 2020 (January)